Zinc finger DHHC-type palmitoyltransferase 13-mediated S-palmitoylation of GNA13 from Sertoli cell-derived extracellular vesicles inhibits autophagy in spermatogonial stem cells - Heran Cao; Huihui Gao; Yan Li; Long Li; Shujuan Liu; Tianqi Jin; Yang Wang; Ye Gong; Shuiqiao Yuan; Wuzi Dong (Cell Communication and Signaling)
Abstract Extracellular vesicles (EVs) originating from testicular somatic cells act as pivotal intermediaries in cell signaling crosstalk between spermatogenic cells and the testicular microenvironment. The intricate balance between palmitoylation and depalmitoylation governs the positioning of protein cargos on the membrane, thereby influencing cellular activities by concentrating these proteins in EVs for delivery to recipient cells. Here, we reveal that GNA13 undergoes specific S-palmitoylation at Cys14 and Cys18 residues in Sertoli cells (SCs), a modification essential for its localization to the plasma membrane. We identify DHHC13, a member of the zinc finger DHHC-type palmitoyltransferase family that catalyzes protein S-palmitoylation, as the enzyme responsible for this critical post-translational modification. Additionally, GNA13 palmitoylation is indispensable for its selective enrichment in EVs emanating from SCs. Intriguingly, we discovered the presence of palmitoylated GNA13 in SC-derived EVs significantly downregulates autophagy levels in spermatogonial stem cells (SSCs), and the inhibition of GNA13 palmitoylation attenuates its interaction with ARHGEF12 which leads to diminished RhoA activity and consequent elevation of autophagy in SSCs. Our results illuminate the crucial role of DHHC13-mediated GNA13 S-palmitoylation in modulating autophagy levels in SSCs through SCs-derived EVs, suggesting that PM-GNA13-EV may serve as a potential candidate for further exploration in addressing fertility-related challenges during spermatogenesis.